Envolvimento dos sistemas purinérgico, colinérgico e dopaminérgico na neurotoxicidade induzida por metais e agrotóxicos em peixe-zebra (Danio rerio) - Altenhofen, Stefani (2017)
Neurotoxic agents, such as pesticides, organic solvents and metals, are capable to alter normal CNS activity. Manganese (Mn) is a metal found in the environment, which when in excess, accumulates in the CNS making it a potential hazard to health. In addition to Mn, other neurotoxic agents can cause changes, leading to deficits in neurotransmission systems. The growth of crop pests has exponentially increased the use of agrochemicals to maintain plantations. The fungicide tebuconazole is a triazole used in crops, such as barley, wheat, peanuts and orchard fruits and related to behavioral and oxidative changes. The insecticide dichlorvos, belongs to organophosphate family, acts through the acetylcholinesterase (AChE) inhibition, leading to hyperstimulation of cholinergic receptors. Cholinergic system is characterized by the action of acetylcholine (ACh) on muscarinic and nicotinic receptors. The level of this molecule is regulated by acetylcholinesterase (AChE), which catalyzes degradation of ACh into choline and acetate. Purinergic system is characterized by the action of ATP and adenosine on purinoreceptor P2 and P1, respectively. The levels of these molecules are regulated by ectonucleotidases, which constitute the extracellular cascade for ATP hydrolysis to adenosine. Adenosine can be subsequently deaminated to inosine by action of adenosine deaminase (ADA). Dopamine (DA), synthesized from L-DOPA, is the neurotransmitter of the dopaminergic system and it acts through its D1-D5 receptors, controlling the start and execution of movement. This study aims to evaluate the effects of exposure to manganese and pesticides, such as dichlorvos and tebuconazole, on behavioral parameters in larval and adult zebrafish, as well as its effects on purinergic, cholinergic and dopaminergic signaling. Exposure to MnCl2 in the early stages of development (1 hpf - 5 dpf) was able to reduce the distance traveled, absolute turn angle and mobile time of the larvae at 5, 7 and 10 dpf. In addition, it caused an increase in TH levels at 5 and 7 dpf, followed by a reduction at 10 dpf. There was also an increase in markers of cell death. In adult animals, exposure during 96 hours caused a reduction in distance traveled, number of line crossings and absolute turn angle, and an inhibition on memory acquisition through the inhibitory avoidance task. In addition, adult animals exposed to MnCl2 showed increased levels of markers of cell death, TH and DOPAC (3,4-dihydroxyphenylacetic acid) in the brain. The 96-hour exposure to this metal was also able to inhibit the NTPDases and ecto-ADA activities and to reduce ADA2.1-mRNA transcripts, besides for increasing ADP levels and reducing the amount of AMP, ADO and INO in the incubation medium. Tebuconazole was able to increase the ocular distance of larvae at 5 dpf and reduce the exploratory behavior of these animals, and still decrease the locomotor activity of 96 hours exposed adult zebrafish. Moreover, this fungicide decreased AChE activity in both 5 dpf larvae and brains of adult animals. Exposure to dichlorvos (1 hpf - 7 dpf) reduced body length, heartbeat rate and larval surface at 7 dpf as well as affected the escape capacity of larvae at 7 and 14 dpf. Further, it reduced exploratory behavior at 7 and 14 dpf, maintaining this pattern when animals became young adults at 30 dpf, and adults at 70 dpf. However, the analysis performed at 120 dpf showed a recovery of behavioral activity equal to the control. In addition, the analysis of exposure to dichlorvos in the early stages of development at 120 dpf on the enzymes of the purinergic system, showed that this insecticide is able to elevate the ecto-5'-nucleotidase activity and reduce the ecto-ADA activity. The results showed that neurotoxic agents, such as Mn, dichlorvos and tebuconazole, play a role in the larval and adult behavior of zebrafish, and affect different neurotransmission systems. Such behavioral changes may be associated with the deficits observed in neurochemical and molecular mechanisms investigated.